2D Metal–Organic Frameworks as Competent Electrocatalysts for Water Splitting - Wang, Chao‐Peng; Lin, Yu‐Xuan; Cui, Lei; Zhu, Jian; Bu, Xian‐He (Small (Weinheim an der Bergstrasse, Germany), 2023)
Hydrogen, a clean and flexible energy carrier, can be efficiently produced by electrocatalytic water splitting. To accelerate the sluggish hydrogen evolution reaction and oxygen evolution reaction kinetics in the splitting process, highly active electrocatalysts are essential for lowering the energy barriers, thereby improving the efficiency of overall water splitting. Combining the distinctive advantages of metal–organic frameworks (MOFs) with the physicochemical properties of 2D materials such as large surface area, tunable structure, accessible active sites, and enhanced conductivity, 2D MOFs have attracted intensive attention in the field of electrocatalysis. Different strategies, such as improving the conductivities of MOFs, reducing the thicknesses of MOF nanosheets, and integrating MOFs with conductive particles or substrates, are developed to promote the catalytic performances of pristine MOFs. This review summarizes the recent advances of pristine 2D MOF‐based electrocatalysts for water electrolysis. In particular, their intrinsic electrocatalytic properties are detailly analyzed to reveal important roles of inherent MOF active centers, or other in situ generated active phases from MOFs responsible for the catalytic reactions. Finally, the challenges and development prospects of pristine 2D MOFs for the future applications in overall water splitting are discussed. Pristine 2D metal–organic frameworks (MOFs) for electrocatalytic water splitting are reviewed to reveal different strategies to improve their catalytic performance. Their intrinsic catalytic properties are detailly analyzed to disclose important roles of inherent MOF active centers, or other in situ derived active phases responsible for the electrocatalysis.